Transcriptome Analysis of Chilling-Imbibed Embryo Revealed Membrane Recovery Related Genes in Maize - He, Fei; Shen, Hangqi; Lin, Cheng; Fu, Hong; Sheteiwy, Mohamed S.; Guan, Yajing; Huang, Yutao; Hu, Jin (Frontiers in Plant Science, 2017)
The delayed seed germination and poor seedling growth caused by imbibitional chilling injury was common phenomenon in maize seedling establishment. In this study, RNA sequencing technology was used to comprehensively investigate the gene expressions in chilling-imbibed maize embryo and to reveal the underlying mechanism of chilling injury at molecular level. Imbibed seeds for 2 hours at 5°C (LT2) were selected and transcriptomic comparative analysis was performed. Among 327 DEGs indentified between dry seed (CK0) and LT2, 15 specific genes with plasma membrane (PM) relevant functions belonging to lipid metabolism, stress, signaling and transport were characterized, and most of them showed down-regulation pattern under chilling stress. When transferred to 25°C for recovery (LT3), remarkable changes occurred in maize embryo. There were 873 DEGs including many PM related genes being identified between LT2 and LT3, some of which showing significant increase after 1 hour’s recovery. Moreover, 15 genes encoding intracellular vesicular trafficking proteins were found to be exclusively differential expressed at recovery stage. It suggested that the intracellular vesicle trafficking might be essential for PM recovery through PM turnover. Furthermore, transcriptome analyses on imbibed embryos under normal condition (25°C) were also made as a contrast. A total of 651 DEGs were identified to mainly involved in protein metabolism, transcriptional regulation, signaling and energy productions. Overall, the RNA-Seq results provided us a deep knowledge of imbibitional chilling injury on plasma membrane and a new view on PM repaired mechanism during early seed imbibition at transcriptional level. The DEGs identified in this work would be useful references in future seed germination research.